Rice production by SRI technique - Lal, Shankar; Renu, Renu; Singh, Udai B; Yadav, Ramesh Chandra (Indian Farming, 2015)
System of Rice Intensifiction has been adopted in rice production asit follows a more comprehensive approach addressing variousmanagement practices simultaneously with promising results. This technology has many advantages over the conventional system and shows better and higher yields with lower inputs.